IMPROVEMENT OF TEACHER COMPETENCE IN THE LEARNING PROCESS IMPLEMENTATION OF THE INDEPENDENT CURRICULUM BASED ON STRENGTHENING THE PANCASILA-BASED STUDENTS PROFILE THROUGH ACADEMIC SUPERVISION DIRECTIVE METHOD AT SDN SONOKWIJENAN II / 96 SURABAYA - Indah Antari Mukti (LPPM STAI Muhammadiyah Probolinggo, 2022)
This study aims to describe the improvement of teacher competence in the learning process. Implementation of an independent curriculum based on strengthening the profile of Pancasila students through academic supervision of the directive method. The method that will be used in this research is School Action Research. This action research was carried out at SDN Sonokwijenan II / 96 Surabaya, which was carried out starting April 2022. Each research basically has a different way to get data on a subject or object to be studied. In order to get good, valid and reliable data, a clear approach is needed. Based on the approach taken, it can be used to plan the research to be carried out. This study uses school action research, with the following steps: determining the focus of the problem, planning action, implementing actions accompanied by observation, interpretation and replication. Results of School Action Research (PTS) and analysis of coaching results. Through academic supervision, the directive method can improve the ability of teachers in the preparation of teaching modules based on strengthening the profile of Pancasila students at SDN Sonokwijenan II / 96 Surabaya. The learning implementation plan assessment score increased by 27.9% from the first cycle with an average of 3.4 to an average of 4.4 in the second cycle, while the learning implementation assessment score increased 16.8% from the first cycle with an average of 3.7 to an average of 4.3 in the second cycle .